Baseline lung allograft dysfunction in primary graft dysfunction survivors after lung transplantation. (November 2021) - Li, David; Weinkauf, Justin; Kapasi, Ali; Hirji, Alim; Varughese, Rhea; Lien, Dale; Nagendran, Jayan; Halloran, Kieran
Abstract: Background: Primary graft dysfunction (PGD) after lung transplantation has previously been associated with increased risk of death and chronic lung allograft dysfunction (CLAD), but the relationship to baseline lung allograft dysfunction (BLAD), where graft function fails to normalize, is not known. Methods: We reviewed all double lung transplant recipients transplanted in our program 2004–2016. We defined PGD and CLAD as per recent consensus definitions and BLAD as failure to achieve both FEV1 and FVC ≥80% predicted on 2 consecutive tests ≥3 weeks apart. We used logistic and proportional hazards regression to test the association between severe high-grade PGD (PGD3) with BLAD and CLAD respectively, adjusting for known and identified confounders. Results: 446 patients met inclusion criteria and 76 (17%) developed PGD3 at 48- or 72-h post-transplant. PGD3 occurred more frequently in patients with interstitial lung disease or pulmonary vascular disease, those with higher BMIs and recipients of older donors. PGD3 was associated with more frequent (58% vs. 36%; p = 0.0008) and more severe BLAD (p < 0.0001) and increased BLAD risk in an adjusted model (OR 2.00 [95% CI 1.13–3.60]; p = 0.0182). PGD3 was not associated with CLAD frequency, severity or time to CLAD onset in an adjusted model (HR 1.10 (95% CI 0.64–1.78), p = 0.7226). Conclusion: Severe PGD was associated with increased risk and severity of BLAD but not CLAD. The mechanisms via which PGD may mediate baseline function warrant further investigation. Highlights: Primary graft dysfunction (PGD) is severe lung injury early post-transplant. Baseline lung allograft dysfunction (BLAD) is failure to achieve normal peak lung transplant function. PGD survivors had an increased adjusted risk of BLAD. Chronic lung allograft dysfunction (CLAD) was not increased in PGD survivors.